Dr. Amiril Sahab produces 5 products from Tamanu tree seeds - Nur Hartini, Mohd Hatta (2022)
PEKAN, 19 October 2022 - Tamanu tree (Bintangor Laut) is a common plant on the east coast as it grows abundantly along the east coast of Peninsular Malaysia.